2007
DOI: 10.5194/bg-4-941-2007
|View full text |Cite
|
Sign up to set email alerts
|

Growth and specific P-uptake rates of bacterial and phytoplanktonic communities in the Southeast Pacific (BIOSOPE cruise)

Abstract: Abstract. Predicting heterotrophic bacteria and phytoplankton specific growth rates (µ) is of great scientific interest. Many methods have been developed in order to assess bacterial or phytoplankton µ. One widely used method is to estimate µ from data obtained on biomass or cell abundance and rates of biomass or cell production. According to Kirchman (2002), the most appropriate approach for estimating µ is simply to divide the production rate by the biomass or cell abundance estimate. Most methods using this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 112 publications
3
17
0
Order By: Relevance
“…5a and 5b), our size assumption combined with the cellular abundance selected for our simulations seems to give a satisfying first approximation of the expected nutrient fluxes for the western basin at least. Concerning cellular growth rate, values are in the range of reported values for osmotrophs in the oceans (Duhamel et al, 2007). Although the estimation of osmotrophs growth rate in oceanic environment is still subject to debate, it has been suggested that phytoplankton growth rate are well below their maximum growth rates and that values below 0.5 d −1 are consistent with the existing knowledge on the relationship between elemental composition and physiological state in phytoplankton (Maranon, 2005).…”
Section: Discussionsupporting
confidence: 72%
“…5a and 5b), our size assumption combined with the cellular abundance selected for our simulations seems to give a satisfying first approximation of the expected nutrient fluxes for the western basin at least. Concerning cellular growth rate, values are in the range of reported values for osmotrophs in the oceans (Duhamel et al, 2007). Although the estimation of osmotrophs growth rate in oceanic environment is still subject to debate, it has been suggested that phytoplankton growth rate are well below their maximum growth rates and that values below 0.5 d −1 are consistent with the existing knowledge on the relationship between elemental composition and physiological state in phytoplankton (Maranon, 2005).…”
Section: Discussionsupporting
confidence: 72%
“…Indeed, on a per cell level, P‐Euk presented CO 2 fixation rates roughly an order of magnitude higher than picocyanobacteria and this relationship held after normalizing to biovolume, although results strongly depended on cell size estimates. Actually, data from the literature vary widely, and cell size estimates obtained using flow cytometry are to be taken with caution (Duhamel et al ; Tzur et al ). Using calibration beads, our estimates indicate that the populations of protists sorted here were smaller than 5 μ m (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The isometric scaling of phytoplankton photosynthesis with cell size was first demonstrated using size fractionated measurements of CO 2 fixation rates (Marañón et al ; Duhamel and Moutin ) and later verified using measurements in flow‐cytometry–sorted groups of phytoplankton similar to this study (Jardillier et al ; Grob et al ; Rii et al ). Calculated biomass‐normalized rates of CO 2 fixation, a proxy for growth rates (Marañón ; Duhamel et al ), using conversion factors in Hartmann et al (), were 0.56 ± 0.11, 0.78 ± 0.27, 0.58 ± 0.06, and 0.44 ± 0.08 d −1 for Prochlorococcus , Synechococcus , P‐Euk_A, and P‐Euk_B, respectively. Although comparable to values previously reported (Jardillier et al ; Rii et al ), these estimates should be taken with caution as they are highly dependent on volume‐specific C conversion factors and equations that are used to calculate biovolume and C content (Duhamel et al ), particularly considering the much wider size range for P‐Euk compared to picocyanobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Growth rates calculated based on changes in average partP concentration (i.e. in P biomass) between T0 and T144 were 0.02, 0.20 and 0.16 d −1 in the control, NP32 and NP50 treatments, respectively, while growth rates based on average specific Pi uptake rate (ratio of Pi uptake rate to partP; Duhamel et al 2007) at T144 were 0.14 ± 0.03, 2.11 ± 0.53 and 2.94 ± 0.85 d −1 in the control, NP32 and NP50 treatments, respectively. The higher growth rates based on specific Pi uptake rates compared to changes in P biomass (or cell abundance) suggests that a large fraction of the Pi taken up by the cells was not transformed into biomass and must have been excreted as both Pi and DOP.…”
Section: Effect Of Short-term Change In N and P Availability On Dop Dmentioning
confidence: 98%